2019
DOI: 10.1371/journal.pntd.0007032
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles from Echinococcus granulosus larval stage: Isolation, characterization and uptake by dendritic cells

Abstract: The secretion of extracellular vesicles (EVs) in helminth parasites is a constitutive mechanism that promotes survival by improving their colonization and adaptation in the host tissue. In the present study, we analyzed the production of EVs from supernatants of cultures of Echinococcus granulosus protoscoleces and metacestodes and their interaction with dendritic cells, which have the ability to efficiently uptake and process microbial antigens, activating T lymphocytes. To experimentally increase the release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 96 publications
(123 reference statements)
4
73
1
Order By: Relevance
“…The particle size distribution of the vesicles was distributed around 50-150 nm and peaked at a mean diameter of 98.47 nm (Fig. 1b), which had the prototypical size characteristic of exosome-like vesicles and was consistent with exosomes from other parasites [11,24,28,[36][37][38][39]. This data indicated that we successfully isolated and purified exosomelike vesicles from C. pisiformis.…”
Section: Size and Morphological Analysis Of C Pisiformis-derived Exosupporting
confidence: 67%
See 2 more Smart Citations
“…The particle size distribution of the vesicles was distributed around 50-150 nm and peaked at a mean diameter of 98.47 nm (Fig. 1b), which had the prototypical size characteristic of exosome-like vesicles and was consistent with exosomes from other parasites [11,24,28,[36][37][38][39]. This data indicated that we successfully isolated and purified exosomelike vesicles from C. pisiformis.…”
Section: Size and Morphological Analysis Of C Pisiformis-derived Exosupporting
confidence: 67%
“…Recently, helminthes-derived exosomes or extracellular vesicles (EVs) have been proved a new paradigm in the study of parasite-host communication [7,8]. Exosomes are nano-scale (30-150 nm) membrane-bound vesicles that are released into the extracellular environment via the fusion of the plasma membrane with the membrane of multi-vesicular bodies (MVBs) [9][10][11]. These vesicles are produced by normal [12] and pathological cells [13] and can be obtained from extracellular fluids, including urine [14], blood plasma [15], breast milk [16], saliva [17], and cerebrospinal fluid [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The particle size distribution of the vesicles was distributed around 50-150 nm and peaked at a mean diameter of 98.47 nm (Fig. 1b), which had the prototypical size characteristic of exosome-like vesicles and was consistent with exosomes from other parasites [10,23,27,[38][39][40]. This data indicated that we successfully isolated and puri ed exosome-like vesicles from T. pisiformis cysticercus.…”
Section: Size and Morphological Analysis Of T Pisiformis Cysticercussupporting
confidence: 65%
“…Scale-bars: 2 μm in platyhelminths [47][48][49]. Some membrane-bound proteins have been demonstrated, including important proteins such as binding proteins, heat-shock proteins, enzymatic and transmembrane proteins [50]. Sotillo et al [51] showed the expression profiles of tegument proteins upregulated over 3 h to 5 days during transformation of cercariae to schistosomula in S. mansoni.…”
Section: Discussionmentioning
confidence: 99%